A Perkawinan Dini di Era Modern: Analisis Relevansi, Tantangan Penetapan dan Implementasi Batas Minimal Usia Nikah - Anwar, Wirani Aisiyah; Wahyu Sururie, Ramdani; Fautanu , Idzam; Makkulau Wahyu, Andi Rio; Yaekaji, Aisyah (DIKTUM: Jurnal Syariah dan Hukum, 2024)
This article explores the relevance and challenges in implementing marriage age limits to address early marriage issues in the modern era, as stipulated in Article 7 of Law No. 16 of 2019 concerning Marriage in Indonesia. The research aims to reduce the incidence of early marriage and identify obstacles in applying marriage age limits within the Indonesian legal context. The study employs a qualitative method supported by literature review, focusing on normative law through statutory, analytical, and conceptual approaches. The findings indicate that early marriage persists due to societal support and the regulation of marriage age limits under Article 7 of Law No. 16 of 2019, which sets the minimum age for marriage at 19 years for both males and females. In contrast, Thailand sets the minimum age at 17 years for both sexes, reflecting a more egalitarian approach. Despite the age differences, both countries share similarities in technical-administrative procedures. Marriages below the specified age require written permission from the authorities, aimed at providing legal protection and ensuring the readiness of those marrying. These minimum age variations reflect cultural, social, and legal factors in each country, while procedural similarities demonstrate collaborative efforts in regulating early marriages.